The Treatment Effectiveness Assessment (TEA): an efficient, patient-centered instrument for evaluating progress in recovery from addiction - Ling W; Farabee D; Liepa D; Wu LT (Dove Medical Press, 2012)
Walter Ling,1 David Farabee,1 Dagmar Liepa,2 Li-Tzy Wu31Integrated Substance Abuse Programs, University of California, Los Angeles, CA, USA; 2Valley Care Medical Center, Panorama City, CA, USA; 3Department of Psychiatry and Behavioral Sciences, School of Medicine, Duke University Medical Center, Durham, NC, USAAbstract: The fields of addiction medicine and addiction research have long sought an efficient yet comprehensive instrument to assess patient progress in treatment and recovery. Traditional tools are expensive, time consuming, complex, and based on topics that clinicians or researchers think are important. Thus, they typically do not provide patient-centered information that is meaningful and relevant to the lives of patients with substance use disorders. To improve our ability to understand patients’ progress in treatment from their perspectives, the authors and colleagues developed a patient-oriented assessment instrument that has considerable advantages over existing instruments: brevity, simplicity, ease of administration, orientation to the patient, and cost (none). The resulting Treatment Effectiveness Assessment (TEA) elicits patient responses that help the patient and the clinician quickly gauge patient progress in treatment and in recovery, according to the patients’ sense of what is important within four domains established by prior research. Patients provide both numerical responses and representative details on their substance use, health, lifestyle, and community. No software is required for data entry or scoring, and no formal training is required to administer the TEA. This article describes the development of the TEA and the initial phases of its application in clinical practice and in research.Keywords: substance use disorders, global treatment progress, brief instrument, patient-centered